2012
DOI: 10.1097/inf.0b013e3182684d8e
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Transmitted HIV-1 Drug Resistance Mutations in Children and Adolescents in São Paulo, Brazil

Abstract: The presence of X4-tropic variants in more than 80% of our cohort of antiretroviral-experienced children and adolescents with vertical HIV-1 infection indicates a very limited role for CCR5 antagonists as part of salvage regimens for highly treatment-experienced vertically HIV-1-infected patients with extensive antiretroviral drug resistance and limited treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…However, there are several limitations with this approach, including: no phenotypic confirmation, inability to detect minority viral populations, and determinants of X4 tropism residing outside of the V3 region [9]. In the only other study of the ESTA ™ assay in PHIV children, 36 cART-experienced PHIV Spanish children (median age: 14.6 years, range: 10.9–17.0) had an overall prevalence of X4-tropism of 33%, substantially lower than our finding [5]. In general, we demonstrated higher prevalence rates of X4/DM virus using the ESTA ™ assay than those that have used genotypic testing in PHIV children and youth [6, 7].…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…However, there are several limitations with this approach, including: no phenotypic confirmation, inability to detect minority viral populations, and determinants of X4 tropism residing outside of the V3 region [9]. In the only other study of the ESTA ™ assay in PHIV children, 36 cART-experienced PHIV Spanish children (median age: 14.6 years, range: 10.9–17.0) had an overall prevalence of X4-tropism of 33%, substantially lower than our finding [5]. In general, we demonstrated higher prevalence rates of X4/DM virus using the ESTA ™ assay than those that have used genotypic testing in PHIV children and youth [6, 7].…”
Section: Discussioncontrasting
confidence: 54%
“…The presence of X4 or dual-mixed (DM), X4 and R5-tropic HIV, precludes the response to therapy with a R5 antagonist [4]. The few pediatric studies in the literature have reported X4 or DM prevalence rates of 19–33% in cohorts of children on and off antiretroviral therapy[5–7]. However, these studies have primarily used genotypic assays to assess HIV tropism, which may be less accurate and less clinically relevant than phenotypic tropism assays [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other drug families (cell-entry and integrase inhibitors), could be good candidates to control viraemia among pretreated transferred patients in Madrid due to their previous scarce exposure (<1%). However, the presence of X4-tropic variants in over 80% of the cohort of antiretroviral-experienced children and adolescents with vertical HIV-1 infection in Madrid has recently been reported [44]. The authors indicate a very limited role for CCR5 antagonists as part of salvage regimens for highly treatment-experienced vertically infected patients with extensive antiretroviral drug resistance [44].…”
Section: Discussionmentioning
confidence: 95%
“…MVC), which are only active against viral populations that use the CCR5 co‐receptor for cell entry. The proportion of perinatally infected adolescents with R5 variants, for whom MVC is a potential option, is highly variable within cross‐sectional studies 183, 184. Co‐receptor tropism should be performed within 3 months of the proposed treatment switch that includes MVC for those with detectable viraemia.…”
Section: When To Switch Resistance Testing and Second And Subsequentmentioning
confidence: 99%